Penetapan Tersangka Tindak Pidana Narkotika Terhadap Anggota Polri Tanpa Adanya Barang Bukti - Rumangun, Johan Pieter Elia (PATTIMURA Legal Journal, 2024)
Introduction: Determining a suspect for a narcotics crime against a member of the National Police without any evidence is a complex and sensitive legal issue. Purposes of the Research: This case highlights the procedures for determining suspects in a law enforcement environment, where the integrity and public trust in the National Police institution is at stake. Methods of the Research: This type of research is normative juridical in nature. The research type is descriptive-analytical. Sources of legal materials use primary legal materials and secondary legal materials. Techniques for collecting legal materials through literature study and qualitative analysis of legal materials. Results Originality of the Research: The research results show that although physical evidence is very important in enforcing criminal law, the determination of suspects can be carried out based on digital evidence or other adequate information, provided that strict legal procedures are followed to ensure fairness and transparency. However, determining suspects without physical evidence against members of the National Police must be carried out very carefully to avoid the appearance of abuse of authority or actions that could harm the image of the police.